Предмет: Алгебра,
автор: Sasha24242424
Решите пожалуйста
Упростите алгебраическое выражение:
3а-(2а-(а-7))=?
6d-(3d-((k-8d)-2k))=?
( можно не только ответ а решение)
Ответы
Автор ответа:
0
3а - (2а - (а - 7)) =
3а - (2а - а +7) =
3а - 2а + а - 7 =
4а - 2а - 7 =
2а - 7
6d - (3d - ((k - 8d) - 2k)) =
6d - (3d - (k - 8d - 2k)) =
6d - (3d - k + 8d + 2k) =
6d - 3d + k - 8d - 2k =
-5d - k
3а - (2а - а +7) =
3а - 2а + а - 7 =
4а - 2а - 7 =
2а - 7
6d - (3d - ((k - 8d) - 2k)) =
6d - (3d - (k - 8d - 2k)) =
6d - (3d - k + 8d + 2k) =
6d - 3d + k - 8d - 2k =
-5d - k
Похожие вопросы
Предмет: Английский язык,
автор: Аноним
Предмет: Алгебра,
автор: homostupid
Предмет: Математика,
автор: even62
Предмет: Математика,
автор: deer1116
Предмет: Геометрия,
автор: Aslan0505